Opportunities Using Boron to Direct Reactivity in the Organic Solid State - Campillo-Alvarado, Gonzalo; MacGillivray, Leonard R. (Synlett, 2020)
This Account describes work by our research group that highlights opportunities to utilize organoboron molecules to direct chemical reactivity in the organic solid state. Specifically, we convey a previously unexplored use of hydrogen bonding of boronic acids and boron coordination in boronic esters to achieve [2+2]-photocycloadditions in crystalline solids. Organoboron molecules act as templates or ‘shepherds’ to organize alkenes in a suitable geometry to undergo regio- and stereoselective [2+2]-photocycloadditions in quantitative yields. We also provide a selection of publications that served as an inspiration for our strategies and offer challenges and opportunities for future developments of boron in the field of materials and solid-state chemistry.1 Introduction1.1 Template Strategy for [2+2]-Photocycloadditions in the Solid State2 Boronic Acids as Templates for [2+2]-Photocycloadditions in the Solid State2.1 Supramolecular Catalysis of [2+2]-Photocycloadditions in the Solid State Using Boronic Acids3 Boronic Esters as Templates for [2+2]-Photocycloadditions in the Solid State3.1 Application of Photoproducts: Separation of Thiophene from Benzene through Crystallization3.2 Crystal Reactivity of B←N-Bonded Adducts: The Case of Styrylthiophenes4 Conclusions and Perspectives
Keywords: boron; [2+2]-photocycloadditions; solid-state chemistry; supramolecular chemistry; hydrogen bond; boron coordination